2021
DOI: 10.1002/pen.25796
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of polyimide/carbon nanotube composite films with electromagnetic wave absorption performance

Abstract: The polyimide (PI)/carbon nanotube (CNT) films including 3,3′,4,4′‐biphenyl tetracarboxylic dianhydride (BPDA), p‐phenylenediamine (p‐PDA), and CNTs were prepared, which have prominent electromagnetic (EM) wave absorption performance. Experimental analyses of the mechanical properties, thermal stabilities, coefficient of thermal expansion (CTE), the glass transition temperature (Tg), and EM parameter revealed the beneficial effects of the CNTs on the resulting composite films. In particular, when the content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…With the development of radar detection technology, the improvement of the stealth performance of modern aircrafts has become a research focus. [1,2] Here, electromagnetic wave absorbing materials are a key to achieve the stealth performance by converting incident microwave into thermal energy via electrical/magnetic losses. [3,4] Today, electromagnetic wave absorbing materials with lightweight, high heat resistance, high mechanical strength, and good electromagnetic absorption ability are needed to meet the new requirements.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of radar detection technology, the improvement of the stealth performance of modern aircrafts has become a research focus. [1,2] Here, electromagnetic wave absorbing materials are a key to achieve the stealth performance by converting incident microwave into thermal energy via electrical/magnetic losses. [3,4] Today, electromagnetic wave absorbing materials with lightweight, high heat resistance, high mechanical strength, and good electromagnetic absorption ability are needed to meet the new requirements.…”
Section: Introductionmentioning
confidence: 99%
“…It is urgent to develop high-performance EMWA materials that are "thin, light, wide, and strong." [5][6][7] In the field of EMWA materials, single functional materials such as coated EMWA materials cannot meet the increasing needs of modern technological development. [8][9][10] In recent years, the works focus on the EMWA materials with integration of the structure and function have been reported, realizing the reduction of weight and enhancing the comprehensive performance of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of electromagnetic contamination protection and stealth detection technology, people have higher and higher requirements for EMWA materials with the continuous development of the material field, especially structural EMWA materials. It is urgent to develop high‐performance EMWA materials that are “thin, light, wide, and strong.” [ 5–7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Ju et al [ 34 ] reported the fabrication of multiwalled CNTs/polyacrylonitrile fibers by electrospinning, which exhibited an electrical conductivity of 96 S/m at a nanotube loading of 3 wt.%. Jiang et al [ 35 ] prepared multiwalled CNTs/PI composites, including 3,3′,4,4′-biphenyltetracarboxylic dianhydride (BPDA), p-phenylenediamine (p-PDA), which showed the effective absorption bandwidth of 2.72 GHz with the matching thickness of only 2.0 mm when the content of CNTs was 6 wt.%, and the tensile modulus and tensile strength of the composites all reached their maximum values of 4.9 GPa and 281.3 MPa when the content of CNTs was 0.5 wt.%, respectively.…”
Section: Introductionmentioning
confidence: 99%